Are Academics Committed to Accounting Ethics Education? - Gunz, Sally (Journal of business ethics, 1998)
This paper reviews the current commitment of accounting academics to teaching accounting ethics. In the course of the review it assesses the recent initiative of the American Accounting Association; namely, Ethics in the Accounting Curriculum: Cases and Readings, 1994. This collection of cases has not been widely adopted despite an identified lack of case materials available to those teaching accounting ethics. The question becomes whether the lack of adoption suggests that accounting academics are not particularly interested in incorporating ethical issues in the classroom or whether there are difficulties with the quality of the collection. The paper continues by examining the current state of research in accounting ethics and again asks what this tells us about commitment to teaching accounting ethics. While the conclusions of this examination are far from definitive, there are signs that all is not well with the accounting ethics discipline.